Lobular Carcinoma in Situ with Atypical Mass Presentation: a Case Report - Luciana Graziano; Almir Galvão Vieira Bitencourt; Camila Souza Guatelli; Juliana Alves Souza; Cynthia Aparecida Bueno de Toledo Osório; Miriam Rosalina Brites Poli; Elvira Ferreira Marques (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Lobular carcinoma in situ (LCIS) is associated with an increased risk of breast cancer and accounts for 1 to 2% of all breast cancers. LCIS diagnosis currently remains one of the major identifiable risk factors for subsequent breast cancer development. Imaging methods are becoming increasingly sensitive, and the consequent detection of small lesions and subtle abnormalities increases the chance of detection of in situ and invasive carcinomas, leading to a reduction in mortality. This report describes a case of a palpable complaint with abnormal imaging findings, including a solid LCIS mass.